Financial Information System Analysis of YPPI Rembang University with the PIECES Method - Nita Sari; Siti Nur Sikhah Arum Yuliyanti; A. Aviv Mahmudi (Formosa Journal of Computer and Information Science, 2024)
This study aims to analyze the use of the Financial System at YPPI Rembang University through the PIECES method. Which consists of performance (performance), information (information), economy (economy), control (control), efficiency (efficiency), and service (service). This study measures the level of overall satisfaction with the financial system that has been implemented. In addition, this study also aims to determine the weaknesses and deficiencies of the system, which in the future will become a benchmark in system development. In this study, data collection was carried out by distributing questionnaires to 12 respondents. The results obtained from the respondents to the six indicators proposed are that they have an average of 3.73, which means that users already feel satisfied with the existing financial system